Validity and Effectiveness of Problem Based Learning E-Book Integrated with Indigenous Culture to Enhance Digital Literacy Skills in the Society 5.0 Era - Margalita, Shella; Susantini*, Endang; Kuntjoro, Sunu; Ali, Marlina (Universitas Syiah Kuala, 2025)
21st-Century Education in the Society 5.0 Era emphasizes the development of skills relevant to modern demands, such as digital literacy. The skill can be enhanced through four key indicators: photo-visual skills, branching skills, reproductive skills, and information skills, which collectively support the ability to access and understand information from various digital sources. However, digital literacy levels in Indonesia remain relatively low. To address this, an e-book has been developed as a learning resource that integrates the indigenous culture of Sumur Panguripan in Surabaya with ecosystem-related topics. This study aims to produce a valid and effective problem-based learning e-book that integrates the indigenous culture of Sumur Panguripan to improve students' digital literacy skills. The research follows the ASSURE model, which includes the following stages: Analyze Learners, State Objectives, Select Methods, Media, and Materials, Utilize Media and Materials, Require Learner Participation, and Evaluate and Revise. Data analysis was conducted using descriptive quantitative methods. The findings indicate that the problem-based learning e-book achieved a high Aikens V validity index score across content feasibility, presentation, and language aspects, categorizing it as valid. Moreover, the e-book demonstrated high effectiveness in enhancing students' digital literacy. The results confirm that this problem-based learning e-book, integrated with the indigenous culture of Sumur Panguripan, is capable of significantly improving digital literacy skills in the Society 5.0 era.